Performance analysis and simulation of vertical gallium nitride nanowire transistors - Witzigmann, Bernd; Yu, Feng; Frank, Kristian; Strempel, Klaas; Fatahilah, Muhammad Fahlesa; Schumacher, Hans Werner; Wasisto, Hutomo Suryo; Roemer, Friedhard; Waag, Andreas (Solid-State Electronics, 2018)
Gallium nitride (GaN) nanowire transistors are analyzed using hydrodynamic simulation. Both p-body and n-body devices are compared in terms of threshold voltage, saturation behavior and transconductance. The calculations are calibrated using experimental data. The threshold voltage can be tuned from enhancement to depletion mode with wire doping. Surface states cause a shift of threshold voltage and saturation current. The saturation current depends on the gate design, with a composite gate acting as field plate in the p-body device.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Gallium nitride; Nanowires; Simulation; Transistor